Simulation of rainfall and seepage flow on unsaturated soil by a seepage-deformation coupled method (2012)
ABSTRACT: This paper presents an application for the analysis of structures formed by un-saturated layered soils subjected to rainfall and seepage flow; the results are part of a current research project on rainfall infiltration. A three - phase coupled infiltra-tion - deformation method for unsaturated soil was used for the numerical analysis. The effects of the water permeability and horizontal drainage on the distribution of seepage flow velocities, saturation, and generation of deformations for an unsaturated layered embankment were investigated. The results show that the generation of deformation on the embankment surface highly depends on the water permeability of the soil. In addition, through horizontal drainage simulations, the advantage of this type of solution for decreasing the pore water pressures on the back of the slope embankment, thus avoiding local failure (erosion), is shown.